Refining Final Report Writing in English for Hospitality Communication through Genre-Specific Move, Service Lexicon Precision, and Contextual Register - Stevani, Margaret; Saragi, Alexander Adrian; Astuti, Peni; Permatasari, Yovita Dyah (English Education : English Journal for Teaching and Learning, 2025)
The research analyzed student writing samples to identify common challenges such as vague conclusions, overuse of passive voice, and syntactic fragmentation by focusing on three key pedagogical components: genre-specific rhetorical moves, service lexicon precision, and contextual register awareness. Findings revealed that students often lacked awareness of professional genre conventions, resulting in ineffective expression of experiential learning and accountability. Through targeted instruction that incorporated move-based modeling with lexical enhancement and discourse-level sensitivity, participants demonstrated significant improvement in clarity, coherence and professional tone. The research underscored the effectiveness of an integrated and genre-informed approach in elevating students’ communicative competence in hospitality reporting tasks could offer implications for curriculum design in ESP contexts.